Kesalahan Berpikir dan Distorsi Memori - Solihan, Sekarrini (Universitas Tanjungpura, 2024)
This study examines the role of teachers in strengthening character education to foster disciplined behavior among students at SMP 23 Pontianak. The background of this research is based on the importance of character education as an effort to shape a generation with disciplined and responsible behavior. This research employs a qualitative method with a literature study approach, where data are gathered from relevant literature sources, including research findings, research reports, journals, or articles. The study results show that teachers play an essential role as role models, motivators, and facilitators in the learning process to build student discipline. Teachers consistently apply disciplinary values through classroom rules, supervision, and persuasive and communicative approaches. This implementation of character education has proven effective in increasing students